Improving the functional preparedness of volleyball players aged 18-22 using recovery measures - Vanyuk, A.; Vindyk, A.; Zakharina, I.; Hrybovska, I.; Pityn, M.; Danylevych, M.; Hrybovskyy, R. (Journal of Physical Education and Sport, 2020)
Studies that conducted on the women's volleyball material show that one of the main reasons for the unsuccessful performances of Ukrainian athletes in this sport is the inability to maintain the optimal level of functional preparedness for a long time. The purpose is to optimize the functional preparedness of female volleyball players aged 18-22 during the competitive period in the annual training cycle using antioxidant recovery measures. Methods: analysis and generalization of scientific and methodological sources; pedagogical observations; pedagogical experiment; testing of physical performance, aerobic capabilities, functional preparedness; functional methods of investigation cardiovascular and antioxidant (nitric oxide synthesis system) systems; methods of mathematical statistics. Results. At first developed the program of recovery measures of antioxidant nature for the volleyball players aged 18-22 during the competition period, which considered the correlation of players' functional preparedness level and their nitric oxide synthesis functional condition level, could be recognized as a modern one. The author's program of recovery measures, which additionally included the use of ecdysterol, allowed to significantly (p>0.05) increase the level of functional capabilities of female volleyball players. Conclusions. Using the recovery activities author's program designed for volleyball players during competition period in the annual training cycle contributed to substantial optimization of functional preparedness and other components of examined female athletes' fitness. The main positive changes were established in physical and aerobic performance, alactate and lactate capacity and volume, anaerobic metabolism threshold, heart rate at PANO, general metabolic capacity, efficiency system of muscular activity energy supply, reserve capacities, levels of general, speed, and power endurance, functional readiness, heart rate efficiency, adaptation capacity of the cardiovascular system, increase in the brachial artery diameter, linear and volumetric blood flow velocity and lower values of the total peripheral vascular resistance, tension index of regulatory mechanisms of the circulatory system and index of vegetative balance.